Kesetaraan dan Keadilan Gender pada Keluarga Pekerja (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2023)
This paper aims to strengthen the concept of gender equality relations in a married couple who work together, as well as how the division of roles in the family and the pattern of husband and wife partnership in managing their household. This paper uses a functionalist structural approach in analyzing modern family phenomena in the application of gender relations in their households. Through this analysis, it is hoped that it will be able to see the understanding that has been cultivated in society related to the parallels of men and women in the family. The results of writing this article show how to build partnerships between married couples in managing the household. According to the functionalist structural theory, the role and involvement of the husband in domestic life remains relevantly applied in modern society. Gender equality relations in working families can be built by equality and justice between husbands, wives, and children in performing all family functions through the equitable division of roles, both in the domestic and social spaces.